The Results of Fostering Legal Awareness in Students Through The Human Rights Law Awareness Student Forum - Fami Miftahulzaman; Endang Sumantri; Dadang Sundawa (Jurnal Civicus, 2021)
This research was based on the condition of students legal awareness in the city of Bandung was still not good, and there were cases of juvenile delinquency at SMAN 27 Bandung. Therefore there was a need for efforts to foster legal awareness in students at SMAN 27 Bandung was through the Human Rights Law Awareness Student Forum. This study aimed to examine the implementation of legal awareness development in students through FPSH HAM SMAN 27 Bandung. This study used a qualitative approach with a descriptive method. Data collection techniques were carried out in this study using interviews, observation, documentation, and literature study. Data analysis techniques were carried out using data reduction, data presentation, conclusions/verification, and data validity. The results obtained from this study are The results of fostering legal awareness in students through FPSH HAMÂ  can have a good impact and benefit on schools, and members of the FPSH HAM, so that the results of the training carried out have added knowledge, understanding, attitudes, and legal behavior to students at SMAN 27 Bandung.